Telomerase expression and telomere length in breast cancer and their associations with adjuvant treatment and disease outcome - Lingeng Lu; Chong Zhang; Gongjian Zhu; Melinda L. Irwin; Harvey A. Risch; Guido Menato; Marco Mitidieri; Dionyssios Katsaros; Herbert Yu (2011)
Telomere length plays important roles in maintaining genome stability and regulating cell replication and death. Telomerase has functions not only to extend telomere length but also to repair DNA damage. Studies have shown that telomerase may increase cancer cell resistance to DNA-damaging anticancer agents; tamoxifen may suppress telomerase expression in breast cancer cells. This study aimed to investigate the role of telomere length and telomerase activity in breast cancer prognosis.qPCR and qRT-PCR were used to analyze telomere length and telomerase expression, respectively, in tumor samples of 348 breast cancer patients. Cox regression analysis was performed to examine telomere length and telomerase expression in association with disease-free survival and cause-specific mortality.Telomere length had no relation to tumor features or disease outcomes. Telomerase expression was detected in 53% of tumors. Larger tumors or aggressive disease were more likely to have telomerase expression. Among patients treated with chemotherapy, high telomerase was found to be associated with increased risk of death (hazard ratio (HR) = 3.15; 95% CI: 1.34 to 7.40) and disease recurrence (HR = 2.04; 95% CI: 0.96 to 4.30) regardless of patient age, disease stage, tumor grade, histological type or hormone receptor status. Patients treated with endocrine therapy had different results regarding telomerase: high telomerase appeared to be associated with better survival outcomes. Telomerase expression made no survival difference in patients who received both chemotherapy and endocrine therapy.Overall, telomerase expression was not associated with disease outcome, but this finding may be masked by adjuvant treatment. Patients with high telomerase expression responded poorly to chemotherapy in terms of disease-free and overall survival, but fared better if treated with endocrine therapy.